KHANDURI APAM: THE REPRESENTATION OF THEOLOGICAL VALUES IN ACEH’S LOCAL CULINARY BANQUET TRADITIONS (International Conference on Social and Islamic Studies, 2021)
Khanduri Apam is one of the traditions or customs of banquets that has been passed down intergenerationally among the Acehnese, especially in the Pidie Regency. The banquet is carried out by consuming local Aceh culinary, namely Apam Cake (Serabi Cake in Bahasa) along with Aceh's typical Kuah Tuhe. As a society with thick Islamic values, Khanduri Apam is held to welcome the month of Rajab and commemorate the Isra' Mi'raj event of the Prophet Muhammad Saw. Khanduri Apam is routinely done every seventh month in the Aceh calendar system, also known as Buleun Apam, or equivalent to Rajab Month in  the Hijri Calendar. This study aims to describe the representation of theological values of the Khanduri Apam tradition among the people of Ulee Tutue Raya Village, Delima District, Pidie Regency, Aceh Province. The research method used is a descriptive analyticalqualitative method with data collection techniques using observation, interviews, and documentation. The informants are determined using the purposive sampling technique. The results of the study show that Khanduri Apam represents 5 theological values, namely: 1) divine values (worship, alms); 2) social values (togetherness, cooperation, tolerance); 3) spiritual value (commemorating Isra 'Mi'raj); 4) ritual values (remembering and praying for the spirits); and 5) intellectual values (preserving customs as well as local cuisine). In representing intellectual values, the Agency of Education and Culture of Pidie Regency also participated by instructing all schools in Pidie Regency, from kindergarten, elementary, to junior high education levels, to hold Khanduri Apam in the schoolenvironment as an effort to maintain the continuity of this tradition among the younger generations, so that they can recognize and maintain these traditions amid the onslaught of contemporary culinary. The Khanduri Apam tradition has a rooted relevance to Islamic values which are considered non contrary to Sharia Law. So that the dialectic of Islam with cultural realities will continue to be intertwined with the values of Islamic theology throughout its history.